PROHIBITIONS OF TRAVEL IN HADITHS: BETWEEN CAUSE AND WISDOM - KIFAH ABDUL QADIR AL-SOURI; MURAD SHIHADA SHAKIB YOUSSEF (Hamdard Islamicus)
The study aimed at revealing the extent to which the prophetic narrations affirming the necessity of a male guardian accompanying a woman in her travel are authentic. It specifically aimed to determine whether the prophetic narrations have provided justifications for prohibiting a woman's travel without a designated male guardian ((وصي. Besides, it aimed to understand the interpretations of jurists (Imams) regarding the ruling on a male guardian accompanying a woman in her travel. The causes of these prohibitions and the wisdom of Islamic law in dealing with women's travel are discussed. Moreover, it is a qualitative study that utilizes the comparative analytical method to analyze the texts of Islamic Law related to the prohibition of women's travel and compare between them. The study concludes that the guardian (“maÍram” مَحْرَمْ)” has various qualifications and that the most cautious approach to ensuring the intended purpose of the requirement for a woman's travel is for the guardian to be an adult, sane, and prohibited from marrying the woman indefinitely. These findings will significantly impact the legal studies on women's travel as they provide deep understanding of women's travel in Islam.